THE EFFECT OF BRAIN BASED LEARNING ON SECOND GRADE JUNIOR STUDENTS’ MATHEMATICS CONCEPTUAL UNDERSTANDING ON POLYHEDRON - I Made Suarsana; Ni Putu Santhi Widiasih; I Nengah Suparta (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2018)
The aim of this study is to examine the effect of Brain Based Learning on second grade junior high school students’ conceptual understanding on polyhedron. This study was conducted by using post-test only control group quasi-experimental design. The subjects of this study were 148 students that divided into three classes. Two classes were taken as sample by using cluster random sampling technique. One of the classes was randomly selected as an experimental group and the other as control group. There were 48 students in experimental group and 51 students in control group. The data were collected with post-test which contained mathematical conceptual understanding on fractions. The post-test consisted of 8 essay question types. The normality and variance homogeny test result showed that the scores are normally distributed and have no difference in variance. The data were analyzed by using one tailed t-test with significance level of 5%. The result of data analysis revealed that the value of t-test = 6,7096 greater than t-table = 1,987, therefore; the null hypothesis is rejected. There is positive effect of Brain-Based Learning on second grade junior students’ conceptual understanding in polyhedron.DOI: http://dx.doi.org/10.22342/jme.9.1.5005.145-156